Raman Thermometry in Water, Ethanol, and Ethanol/Nitrogen Mixtures from Ambient to Critical Conditions - Klima, Tobias C.; Braeuer, Andreas S. (Analytical Chemistry, 2019)
We present investigations into remote liquid temperature sensing with Raman spectroscopy using different evaluation methods for the OH stretching vibration band. Water, ethanol, and ethanol saturated with nitrogen, all as liquids or liquid-like supercritical fluids, are pumped through a heated microcapillary system at elevated pressures. Raman spectra are recorded from the liquid inside the microcapillary and are evaluated with respect to the temperature sensitivity of the OH stretching vibration. The four approaches applied are (i) to evaluate the center position of the Raman OH-band, (ii) the integrated absolute difference spectrum, (iii) the intensity ratio of two regions of the OH-band, and (iv) the intensity ratio of two fitted Gaussian peaks. The temperature range investigated covers from ambient temperature to the component's respective boiling temperature or critical temperature at sub- and supercritical pressures. Precision and robustness of the employed methods are characterized. It is shown that two out of the four methods feature temperature deviations smaller than 5 K at all pressures and that one method can also be applied to liquid mixtures of ethanol and nitrogen. Applicability to other liquids and mixtures is discussed.
Created from Fastlane, Scopus look-up